Pengabdian Masyarakat dengan “Penyuluhan Kesehatan Imunisasi Tetanus Toksoid dan Persiapan Persalinan di Kelas Ibu Hamil Kelurahan Banyurip Kota Pekalongan” - Prajayanti, Hilda; Artanti, Swasti; Ulya, Ni'matul; Andanawarih, Putri (Jurnal ABDIMAS-HIP Pengabdian Kepada Masyarakat, 2025)
Pregnancy and childbirth in a mother is a natural process. In order for the natural process to run smoothly and well and not develop into a pathological condition, mothers can increase their knowledge about signs of high-risk pregnancy through health workers, especially midwives, Posyandu officers and the mass media. The purpose of this community service is to provide information to pregnant women about TT immunization and preparation for childbirth. The method used in this community service activity begins with the opening and introduction of the speakers, then continues with the delivery of health education materials, a question and answer session for participants and finally closing. This activity was attended by 13 pregnant women and an assessment was carried out using the Pre Test and Post Test. With this activity, the Posyandu and Puskesmas, especially pregnant women as the target, felt helped and could increase knowledge in pregnant women.